Macro-element modelling of a dissipative connection for CLT structures. (August 2020) - Marchi, Luca; Trutalli, Davide; Scotta, Roberto; Pozza, Luca
Abstract: Dissipative steel connections for cross-laminated timber buildings are often characterized by biaxial tension-shear interaction in strength and displacement capacity. Detailed continuum models with nonlinear finite elements provide faithful results in simulating the hysteretic response of complex structural systems but generally require too much computational effort. The use of nonlinear macro-elements can strongly increase the efficiency of the analysis with limited decrease of accuracy of the results. In this work, the hysteretic response of a dissipative connection for cross-laminated timber structures was simulated in the OpenSees framework with a macro-element model and compared with results from tests and a continuum finite-element model developed in the Ansys® framework. The accuracy of the macro-element in reproducing the tension-shear interaction has been evaluated in terms of displacement and force domains of the connection. A further comparison between the macro-element and the continuum finite-element modelling was provided analysing the seismic response of cross-laminated timber shear walls with different arrangement of the dissipative connections. Results show that the proposed macro-element can simulate the nonlinear biaxial behaviour of the dissipative bracket and predict the force-displacement response of CLT shear walls with slight conservative underestimation of hysteretic energy dissipation. The macro-element could be implemented in models of buildings for prediction of their dynamic response with a limited computational effort.